1999
DOI: 10.21273/hortsci.34.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod and Cold Treatment Regulate Flowering of Rudbeckia fulgida `Goldsturm'

Abstract: To determine the flowering requirements of Rudbeckia fulgida Ait. `Goldsturm', plants were grown under 9-hour photoperiods until maturity, then forced at 20 °C under one of seven photoperiods following 0 or 15 weeks of 5 °C. Photoperiods consisted of a 9-hour day that was extended with incandescent lamps to 10, 12, 13, 14, 16, or 24 hours; an additional treatment was a 9-hour day with a 4-hour night interruption (NI). Noncooled `Goldsturm' remained vegetative under photoperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown the importance of providing inductive photoperiods to increase the flowering percentage in ornamental crops (Currey and Erwin, 2010;Karlsson and Werner, 2002;Mattson and Erwin, 2003;Rohwer and Heins, 2007;Runkle et al, 1999;Warner, 2010). For example, Currey and Erwin (2010) reported that Kalanchoe spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown the importance of providing inductive photoperiods to increase the flowering percentage in ornamental crops (Currey and Erwin, 2010;Karlsson and Werner, 2002;Mattson and Erwin, 2003;Rohwer and Heins, 2007;Runkle et al, 1999;Warner, 2010). For example, Currey and Erwin (2010) reported that Kalanchoe spp.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, nearly all plants grown under 9-h photoperiods remained vegetative and only 30% of plants flowered under 12 h. The percentage of plants that had visible buds and flowered was greatest (100%) at 14-and 16-h photoperiods. Runkle et al (1999) reported that the number of nodes below the first inflorescence in black-eyed-susan (Rudbeckia fulgida var. sullivantii 'Goldsturm') decreased from 19.7 to 15.6 as the photoperiod increased from 14 to 24 h. Our data were in agreement, because plants under inductive 16-h photoperiods Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous Rudbeckia species and varieties have been reported in experiments of photoperiodic and flowering treatments: R. bicolor var. superba and R. speciosa (Murneek, 1940), Rudbeckia fulgida 'Goldsturm' (Runkle et al, 1999;Elkins & van Iersel, 2020) and Rudbeckia hirta (Beckwith, 1991;Blanchard & Runkle, 2010;Werner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%